Portrait of the Development of Fiscal Autonomy in Supporting Economic Growth of the Kediri City Government - Linawati Linawati; Nur Solikin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
The research aims to analyze the development of fiscal autonomy in supporting the economic growth of the Kediri City Government. Fiscal autonomy shows a region's ability to finance its finances independently, so that dependence on the central government is increasingly minimal. With increasingly strong fiscal autonomy, it will of course support regional economic growth. This research is quantitative research, with descriptive methods. Research data is in the form of secondary data, collected using documentation techniques. The research results show that the degree of fiscal decentralization of the Kediri City Government from 2017 to 2020, and in 2022 is at very low criteria, while in 2021 it will increase at low criteria. There is an increase in the level of fiscal decentralization which is also balanced with economic growth in 2021. The increase in the degree of fiscal decentralization is influenced by PAD revenues and their main components, namely regional taxes and levies. The Kediri City Government must continue to strive to increase its fiscal decentralization. Efforts that may be made by the Kediri City Government to increase its fiscal autonomy, namely by exploring and increasing the potential for PAD revenue, for example developing a regional tax and levy revenue system, continuing to be active in coaching and auditing taxpayers to increase tax compliance, increasing taxpayer data collection. , giving appreciation or rewards to compliant taxpayers, as well as providing support to the real sector to produce goods and services.